Overexpression, purification, crystallization and preliminary X‐ray characterization of the fourth scaffoldin A cohesin from Acetivibrio cellulolyticus in complex with a dockerin from a family 5 glycoside hydrolase. Issue 8 (1st August 2014) - Bule, Pedro; Correia, Ana; Cameron, Kate; Alves, Victor D.; Cardoso, Vânia; Fontes, Carlos M. G. A.; Najmudin, Shabir
<x xml:space="preserve">Abstract</x> Cellulosomes are cell‐bound multienzyme complexes secreted by anaerobic bacteria that play a crucial role in carbon turnover by degrading plant cell walls to simple sugars. Integration of cellulosomal components occurs via highly ordered protein–protein interactions between cohesin modules located in a molecular scaffold and dockerin modules found in cellulosomal enzymes. Acetivibrio cellulolyticus possesses a complex cellulosome arrangement which is organized by a primary enzyme‐binding scaffoldin (ScaA), two anchoring scaffoldins (ScaC and ScaD) and an unusual adaptor scaffoldin (ScaB). A dockerin from a family 5 glycoside hydrolase (GH5), which was engineered to inactivate one of the two putative cohesin‐binding interfaces, complexed with one of the ScaA cohesins from A. cellulolyticus has been purified and crystallized, and data were processed to a resolution of 1.57 Å in the orthorhombic space group P212121.